Variable stars in the bulge globular cluster NGC 6401 - Tsapras, Yiannis (Arxiv, 2016)
We present a study of variable stars in globular cluster NGC 6401. The cluster is only $5.3\degr$ away from the Galactic centre and suffers from strong differential reddening. The photometric precision afforded us by difference image analysis resulted in improved sensitivity to variability in formerly inaccessible interior regions of the cluster. We find 23 RRab and 11 RRc stars within one cluster radius (2.4$\arcmin$), for which we provide coordinates, finder-charts and time-series photometry. Through Fourier decomposition of the RR Lyrae star light curves we derive a mean metallicity of [Fe/H]$_{UVES} = -1.13 ± 0.06$ (${\rm [Fe/H]}_{ZW} = -1.25 ± 0.06$), and a distance of